2001
DOI: 10.1089/105072501753271716
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-131 Treatment of Thyroid Papillary Carcinoma in Patients Undergoing Dialysis for Chronic Renal Failure: A Dosimetric Method

Abstract: Until recently, the therapeutic protocol widely accepted for ablation of the thyroid remnant and for metastases of thyroid papillary carcinoma was the administration of 131I after surgery. However, at present, some data question the usefulness of such treatment in patients considered low risk. The treatment with radioiodine in patients suffering from end-stage renal disease (ESRD) undergoing hemodialysis requires controlled dosages and individualized administration guidelines. The need to include these patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…This effect could act as a compensatory mechanism to neutralize the thyroid dysfunction in order to maintain euthyroid status (129). Treatment with ablative dose of 131 I has been successfully used in the treatment of differentiated thyroid carcinoma in patients on HD (108,(130)(131)(132)(133)(134)(135)(136). HD removes more 131 I from blood than from thyroid and helps to reduce radiation (132).…”
Section: Effects Of Dialysis On Thyroid Functionmentioning
confidence: 99%
“…This effect could act as a compensatory mechanism to neutralize the thyroid dysfunction in order to maintain euthyroid status (129). Treatment with ablative dose of 131 I has been successfully used in the treatment of differentiated thyroid carcinoma in patients on HD (108,(130)(131)(132)(133)(134)(135)(136). HD removes more 131 I from blood than from thyroid and helps to reduce radiation (132).…”
Section: Effects Of Dialysis On Thyroid Functionmentioning
confidence: 99%
“…Other groups have proposed administering larger treatment activities due to rapid iodine clearance from dialysis [6,8]. Finally, a third view suggests that the dose should be the same [5,9]. The trend in our center is to reduce the 131 I activity.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned phenomena increase the risk of patients with CKD exceeding safe doses of I‐131. Studies on the radioactivity of the whole body have shown that radioactivity decreases by 50% within 24–48 h in patients with ESRD treated with I‐131 for differentiated thyroid cancer . HD increases I‐131 clearance, causing so‐called rapid I‐131 clearance, as opposed to the slow I‐131 clearance that depends on residual renal function.…”
Section: Radioactive Iodine Treatment In Patients With Severe Chronicmentioning
confidence: 99%